Effects of ammonium on the CLS of the auxotrophic strain Saccharomyces cerevisiae BY4742 and its modulation by the key proteins Tor1p, Ras2p and Sch9p - Correia, Fernanda Leitão (2014)
Dissertação de mestrado em Genética Molecular